L’alternance codique dans le discours religieux cas de Nader Abou Anas « Comment trouver sa moitié » - Tlaidjia Ghofrane (My University, 2024)
Summary This work, entitled "Code-Switching in Religious Discourse Analysis: Case Study of Nader Abou Anas 'How to Find Your Other Half'," falls within the framework of sociolinguistics, which aims to study language within the Franco-Muslim society. The study is based on an analysis of Nader Abou Anas's speeches, using a video recording of one of his lectures. We use a sociolinguistic approach to analyze the contextual and interactive dimensions of code-switching. According to the results, Nader Abou Anas primarily uses three main languages: Classical Arabic for Quranic and Hadith quotes, French for explaining and developing religious concepts, Colloquial Arabic for more informal interactions and anecdotes, and English to incorporate modern terms. Our corpus analysis allowed us to obtain results similar to our initial hypotheses. ----------------- ملخص هذا العمل الذي يحمل عنوان "التناوب اللغوي في تحليل الخطاب الديني: حالة نادر أبو أنس «كيف تجد نصفك الآخر»" يندرج في إطار علم اللغة الاجتماعي الذي يهدف إلى دراسة اللغة داخل مجتمع المسلمين الفرنسيين. تعتمد الدراسة على تحليل خطابات نادر أبو أنس، بالاستناد إلى تسجيل فيديو لأحد مؤتمراته. نستخدم مقاربة لغوية اجتماعية لتحليل الأبعاد السياقية والتفاعلية للتناوب اللغوي. وفقًا للنتائج، يستخدم نادر أبو أنس ثلاث لغات رئيسية: العربية الفصحى للاقتباسات من القرآن والأحاديث، والفرنسية لشرح وتطوير المفاهيم الدينية، والعربية العامية للتفاعلات غير الرسمية والقصص، والإنجليزية لإدماج المصطلحات الحديثة. سمح لنا تحليل من خلال ما جمعنا بالحصول على نتائج مشابهة لفرضياتنا الأولية ----------------- Résumé Ce travail qui s'intitule l’alternance codique dans l’analyse du discours religieux cas: Nader Abou Anass « Comment trouver sa moitié », s’inscrit dans le cadre de la sociolinguistique qui a pour but d'étudier la langue au sein de la société Franco-musulmane. L’'étude repose sur une analyse e des discours de Nader Abou Anas, en s'appuyant sur un enregistrements vidéo de l’un de ses conférences. On utilise une approche sociolinguistique pour analyser les dimensions contextuelles et interagissant de l'alternance codique. Selon les résultats, Nader Abou Anas utilise principalement quatre langues : l'arabe classique pour les citations du Coran et les hadiths, le français pour expliquer et développer des concepts religieux, l'arabe dialectal pour les interactions plus informelles et les anecdotes, et l'anglais pour intégrer des termes modernes. Notre corpus nous a permis d'obtenir des résultats semblables à nos hypothèses initiales
Keywords: Sociolinguistics; code switching; conference.; اللسانيات الاجتماعية، تبديل الكود، مؤتمر.; sociolinguistique; alternance codique; conférence